2016
DOI: 10.1016/j.ijpe.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Joint economic design of production, continuous sampling inspection and preventive maintenance of a deteriorating production system

Abstract: Standard continuous sampling procedures and tables are conventionally applicable only to continuous production processes that are statistically 'in-control'. Consequently, these standards cannot be used to control quality in deteriorating production processes. Moreover, existing continuous sampling models do not consider interactions with production, inventory and maintenance aspects. In this paper, we attempt to fill these gaps in the literature. We investigate the joint design and optimization of a type-1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Hence, preventive maintenance compliance was checked. Preventive maintenance leads to the prevention and hence reduction of equipment failures or any related issues (Bouslah et al, 2016). In this case, it was found that preventive maintenance compliance for port equipment had an average of 96 percent, which was considered high.…”
Section: Figure 17 Control Chart Of Equipment Downtimesmentioning
confidence: 91%
“…Hence, preventive maintenance compliance was checked. Preventive maintenance leads to the prevention and hence reduction of equipment failures or any related issues (Bouslah et al, 2016). In this case, it was found that preventive maintenance compliance for port equipment had an average of 96 percent, which was considered high.…”
Section: Figure 17 Control Chart Of Equipment Downtimesmentioning
confidence: 91%
“…The two parameters, the critical value 0 and the sample size , must simultaneously satisfy the two nonlinear inequalities (15) and (16). There are infinite values of the combination ( , 0 )which can meet inequalities (15) and (16). The specified value of ( , 0 ) which can simultaneously satisfy (17) and 18is the boundary of all the feasible combinations ( , 0 ).…”
Section: Determination Of Parameters For the Risk Control Schemementioning
confidence: 99%
“…The specified value of ( , 0 ) which can simultaneously satisfy (17) and 18is the boundary of all the feasible combinations ( , 0 ). It means that the combination of ( , 0 ) meeting (17) and (18) can satisfy inequalities (15) and (16).…”
Section: Determination Of Parameters For the Risk Control Schemementioning
confidence: 99%
See 1 more Smart Citation
“…However, it is frequently tackled at the operational level (e.g., the production and maintenance scheduling) (Assid et al, 2015). Because the complexity of the problem highly depends on number of machines or components, majority of the studies have based their modeling approach on singlemachine production maintenance scheduling (Sortrakul et al, 2005;Aggoune and Portmann, 2006;Sortrakul and Cassady, 2007;Yildirim and Nezami, 2014;Zhao et al, 2014;Bouslah et al, 2016a;Bouslah et al, 2016b, Emami-Mehrgani et al, 2016Kang and Subramaniam, 2018;Alimian et al, 2019;Bahria et al, 2019;Liu et al, 2019;Duffuaa et al, 2020;Ghaleb et al, 2020;.…”
Section: Introductionmentioning
confidence: 99%